عقد التسويق الشبكي في ميزان الفقه الإسلامي: دراسة تأصيلية فقهية مقارنة - حجازي، مندي عبدالله محمود Hejazi, Mandi Abdullah Mahmoud (جامعة الأزهر - کلية الدراسات الإسلامية والعربية للبنات بالإسكندرية, 2018)
التسويق الشبكي نظام حديث النشأة ظهر في الولايات المتحدة الأمريكية يهدف إلى كسب أرباح وأموال طائلة دون عناء عن طريق التغرير بالمسوقين المتعاملين به. يعرف التسويق الشبكي باعتباره لقبا وعلما بأنه: أسلوب تسويقي يعتمد على شبكة من العملاء، ويقوم على أساس تجنيد شبكات من الأعضاء الجدد للترويج لمنتجات شركة ما مقابل عمولات مالية. عقد التسويق الشبكي يعد إحدى النوازل الاقتصادية المعاصرة التي تحكم بقواعد وضوابط فقه المعاملات المالية. عقد التسويق الشبكي لا يصح توصيفه على عقد السمسرة ولا على عقد الجعالة ولا على عقد الوكالة وغيرها لما بينه وبين هذه العقود من الفروق الظاهرة الناتجة عن التركيب والشروط المصاحبة.
Network Marketing An emerging system that emerged in the United States of America aims to earn huge profits and money without bothering by deceiving marketers. Network marketing is defined as a title and is defined as: a marketing method that relies on a network of clients and is based on recruiting networks of new members to promote a company's products for a fee. Network marketing contract is one of the modern economic downfalls that govern the rules and regulations of the jurisprudence of financial transactions. The contract of network marketing can not be characterized by the brokering contract or the contract contract or the contract of the agency and others because of the apparent differences between these contracts resulting from the installation and associated conditions.
Keywords: الفقه الإسلامي -- التسويق الشبكي